COMMUNICATION PATTERNS AMONG KIAIS OF NAHDLATUL ULAMA IN THE MADURESE ETHNIC GROUP - Haryono, Akhmad (Universitas Pendidikan Indonesia, 2018)
Research on communication patterns with an ethnographic approach has been conducted by many linguists, but apparently there has hardly been any research on communication patterns within an NU society with its strong paternalistic cultural background. In fact, the uniqueness of this culture also has had a major influence on NU members’ communication patterns in their daily interaction. This study aims to describe the communication patterns among kiais (venerated teachers of Islam) of Nahdlatul Ulama in the Madurese ethnic group (NUME) and account for the factors affecting those patterns of communication. A qualitative method with an ethnographic approach was applied to achieve this research’s objectives. The data were collected through participatory and non-participatory observations, interviews, note-taking, and recording. The recorded data were transcribed and analyzed descriptively using the components of speech analysis, conversational analysis, discourse analysis with pragmatic concepts, and explanation. This study found that giving an honor to the teacher in the NU tradition is an obligation and a tradition that is still maintained. This phenomenon is reflected in the patterns of communication among kiais that have teacher-student ties (KT-KS). The patterns of communication among kiais bearing teacher-students ties (KT-KS) are influenced by situational factors, i.e. formal and informal situations. In an informal situation the KT-KS patterns of communication are influenced by age differences. The age differences that affect the gaps of KT-KS patterns of communication both in formal and informal situations only find expression in the use of speech levels, while in terms of patterns of language selection, tones of voice, body language, and turn-taking, the differences were not found.